1997
DOI: 10.1021/cm960409g
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Multicenter Bonding and Distortions in a Hypothetical Polydithioquinone

Abstract: The electronic properties of polydithioquinone, a hypothetical C 4 S 2 carbon-sulfur polymer related to both tetrathiotetracene and thiothiophthene, are examined using approximate molecular orbital calculations. We focus on a curious pattern of sulfur-sulfur bonding interactions suggested by the band structure calculations, a pattern observed in thiothiophthenes and other molecular analogues of our polymer. The π system of each C 4 S 2 repeat unit contains eight electrons, consistent with a thiothiophthene-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Hypothetical polyketone (CO) n is one example (Scheme ); it is calculated to prefer a helical structure . As hypothetical polymers, polythiene (CS) n , an analogue of polyketone (CO) n , and polydithioquinone, have been suggested, both containing two S chains with S···S interactions. Extended (CO) n and (CS) n polymers show a geometry that we see is analogous to that of all- syn thiophene and furan nanothreads, so it is useful to look at these structures in context…”
Section: Resultsmentioning
confidence: 99%
“…Hypothetical polyketone (CO) n is one example (Scheme ); it is calculated to prefer a helical structure . As hypothetical polymers, polythiene (CS) n , an analogue of polyketone (CO) n , and polydithioquinone, have been suggested, both containing two S chains with S···S interactions. Extended (CO) n and (CS) n polymers show a geometry that we see is analogous to that of all- syn thiophene and furan nanothreads, so it is useful to look at these structures in context…”
Section: Resultsmentioning
confidence: 99%
“…Although the reported synthesized Möbius strips are nonconjugated compounds 6, recent studies on related compounds have shown that the cyclacene‐based materials may exhibit interesting magnetic 1, 3, conducting 22, and electronic 23 properties. Furthermore, due to the close relationship between NLO properties and BLA 24, the Möbius strips and related compounds can be viewed as potential new NLO materials 25, particularly in relation to the special nonlinear optical properties of chiral molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The three-center S-S bond formation in polyconjugated condensed carbon-sulfur polymers like that shown in Scheme 14 has recently been supported theoretically by Hoffmann and co-workers [34,35].…”
Section: Shmentioning
confidence: 67%